1984
DOI: 10.1002/j.1460-2075.1984.tb01951.x
|View full text |Cite
|
Sign up to set email alerts
|

The primary mode of binding of cisplatin to a B-DNA dodecamer: C-G-C-G-A-A-T-T-C-G-C-G.

Abstract: When cisplatin [cis‐ diamminodichloroplatinum (II)] is diffused into pre‐grown crystals of the B‐DNA double‐helical dodecamer C‐G‐C‐G‐A‐A‐T‐T‐C‐G‐C‐G, it binds preferentially to the N7 positions of guanines, with what probably is an aquo bridge between Pt and the adjacent O6 atom of the same guanine. The entire guanine ring moves slightly toward the platinum site, into the major groove. Only three of the eight potential cisplatin binding sites on guanines actually are occupied, and this differential reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
2
2

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 24 publications
4
60
2
2
Order By: Relevance
“…Briefly, the same configuration of pol II, DNA, and RNA as found in the structure containing cis-fPtðNH 3 Þ 2 ðpyÞg 2þ was used for these two complexes. The geometry of the fPtðNH 3 Þ 3 g 2þ moiety was taken from a previous structure where it binds to a B-DNA dodecamer (PDB ID: 5BNA) (39). Docking was achieved by aligning the damaged guanosine base of the two structures.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the same configuration of pol II, DNA, and RNA as found in the structure containing cis-fPtðNH 3 Þ 2 ðpyÞg 2þ was used for these two complexes. The geometry of the fPtðNH 3 Þ 3 g 2þ moiety was taken from a previous structure where it binds to a B-DNA dodecamer (PDB ID: 5BNA) (39). Docking was achieved by aligning the damaged guanosine base of the two structures.…”
Section: Methodsmentioning
confidence: 99%
“…This monoadduct has been observed in the X-ray structure of a platinated dodecanucleotide 72). It has been isolated from DNA by two methods and identified by comparison with model compounds of known structure.…”
Section: Platinum-dna Adductsmentioning
confidence: 97%
“…On average, the confal score improved by 7 after application of the PDB_REDO protocol, but the fraction of reassigned NtC classes varied widely between 0 and 77% in individual structures. The confal values showed significant improvement, for example, in the structure with PDB entry 1d29 (Larsen et al, 1991), while no changes were observed in PDB entry 4i9v (Szulik et al, 2015) and a mixture of increased and lowered confal values were found in PDB entry 5bna (Wing et al, 1984) (Supplementary Table S3). Overall, the PDB_REDO protocol improves the deposited coordinates somewhat, but better molecular templates provided by the NtC classes can constrain the re-refinement more effectively.…”
Section: B-a: Conformers Bridging B-form To A-formmentioning
confidence: 99%